Effect of Crystalloid Preloading on Blood Pressure Stability in Cesarean Section Under Spinal Anesthesia: A Study at Regional General Hospital of Sekarwangi - Danismaya, Irawan; Basri, Burhanuddin; Safariyah, Erna; Hamzah, Amir (Gema Lingkungan Kesehatan, 2025)
Spinal anesthesia is a form of regional anesthesia administered by injecting a local anesthetic into the subarachnoid space and is commonly employed in cesarean section (C-section) procedures. One of its major side effects is hypotension, which, if not properly managed, can compromise uteroplacental perfusion and potentially result in fetal hypoxia, acidosis, and neonatal complications. Preoperative intravenous fluid administration is a preventive strategy aimed at stabilizing blood pressure by increasing central blood volume. This study aimed to examine the effect of preoperative fluid administration on blood pressure stability in C-section patients undergoing spinal anesthesia at the Regional General Hospital at Sekarwangi. A quantitative analytic approach with a pre-test and post-test design was employed. The study population consisted of 62 C-section patients who received spinal anesthesia within the last three months. Data were analyzed using the Paired Samples t-test. The results showed a statistically significant difference in blood pressure before and after fluid administration (p = 0.000 < 0.05), indicating that preoperative fluid administration had a significant effect on blood pressure stability. Future studies are recommended to employ research designs that better control for external variables and address the limitations of the present study.